2017
DOI: 10.1097/jsa.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Treatment of Patellar Instability

Abstract: The treatment of patellar instability is challenging and typically begins with nonoperative methods. Clinical decisions are made on an individual basis and may vary according to a number of factors. First-time patellar dislocations most commonly occur during sports participation. Initial evaluation, including patient history, physical examination, and appropriate imaging, determines care. Although nonoperative treatment consists primarily of regressive immobilization and physical therapy, there is little evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…11 Although there is a lack of concordance in the literature regarding nonoperative treatment of PFI, standard of care treatment includes activity restriction (immobilization), physical therapy and patellar bracing. 12 These options are in line with the answers that we received. There was a wide variability regarding the type of immobilization which included knee immobilizer, knee hinge brace or patellar stabilization brace rather than knee immobilization.…”
Section: Discussionmentioning
confidence: 83%
“…11 Although there is a lack of concordance in the literature regarding nonoperative treatment of PFI, standard of care treatment includes activity restriction (immobilization), physical therapy and patellar bracing. 12 These options are in line with the answers that we received. There was a wide variability regarding the type of immobilization which included knee immobilizer, knee hinge brace or patellar stabilization brace rather than knee immobilization.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have shown that patellar dislocations predispose patients to earlier development of osteoarthritis and other degenerative bone changes, with an 11.9% increase in incidence at 20 years and 40.6% at 25 years [ 14 ]. The recurrence rate after a first-time patellar dislocation can be up to 44% [ 15 , 16 ]. Additionally, the patient’s history of left knee injury at age 4, 12 years before her patellectomy and greater than forty years prior to her official diagnosis of NPS, indicates that the patient was likely susceptible to severe patellar damage from trivial childhood activities.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation protocols vary significantly based on the duration of immobilization and individual needs following the initial dislocation. While some authors recommend immediate mobilization, others suggest immobilization with a cast or brace for up to 6 weeks [29]. Nonetheless, there is a lack of clear evidence supporting the immobilization of the knee after patellar dislocation [9].…”
Section: Conservative Treatmentmentioning
confidence: 99%